Funciones como asistente de: Facturación y Liquidación - Contabilidad Cuentas por Pagar - Tesorería en la Clínica Sánchez Ferrer S.A - Eustaquio Briceño, Yessenia Jackeline (2017)
The purpose of this report is to present my work performance at the Clínica Sánchez Ferrer S.A. in the areas of: Billings and Settlement, Accounts Payable Accounting and Treasury. Since the clinic under study has the only goal of providing health services and taking into account that the quality of patient care includes the atention of administative staff, doctors and auxiliary services providers, I created measures which lead to a continous improvement in the internal controls. I made the “Proyecto de Honorarios Médicos” to minimize the margin of error in the reports of patients attended for each doctor due the inadequate record of the information in the system and therefore decrease the time of sending the reports mencioned above to the doctors’email. I also implemented the payment schedule for doctors and auxiliary test providers (sonography, laboratory, x-ray , tomography, densitometry etc). Thank to this measures, doctors were able to issue their payment vouchers in less time and their timely registration in the accounting system, also to make a better control over payment scheduling and make an estimation in the short term, achieving the timely payment of obligations.